PEMANFAATAN APLIKASI DIGITAL DALAM PENILAIAN SIKAP SISWA DI SEKOLAH DASAR ISLAM TERPADU KONGGO, KAB. DELI SERDANG - Ahmad Salman Farid,; Muhammad Ardiansyah, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The activity of using digital applications in attitude assessment for students of the Konggo integrated Islamic elementary school in Kab. Deli Serdang is carried out with the aim of assisting teachers in monitoring changes in student behavior during class so that they can foster a positive attitude during the learning process and this activity is expected to be a forum for introduction and learning about the use of digital applications so as to shape the teaching and learning process in this Covid-19 era. more creative and interactive. The method of implementing this activity is done by learning by doing. With several stages, namely (1) the planning phase, (2) the implementation phase, (3) the evaluation phase of the application training results. The results of the community service program through the use of digital applications in attitude assessment for students of terpadi Islamic elementary schools in Kab. Deli Serdang is considered successful in increasing the creativity of participants in managing the class and assessing and forming positive attitudes of students during learning